Deepening Trade Reforms in Syria for Improving Competitiveness and Promoting Non-Oil Exports - World Bank (Washington, DC, 2013)
Syria made promotion of non-oil exports one of the main objectives of its development strategy to counter the emerging twin balance of payments and fiscal deficits resulting from secular decline of oil production and exports. To realize this objective, the Government has implemented a number of trade policy reforms and took complementary measures in other policy areas during the 10th five-year plan to improve competitiveness of Syrian products in international markets. Non-oil exports responded strongly to the policy improvements. There is now a wide recognition of the need for further reforms to maintain this momentum. This paper tried to assess the achievement so far, identify the remaining gaps in the trade regime, and recommend follow up measures for broadening and deepening the trade reforms. The principal recommendations are presented in the attached policy matrix. The objective of export incentives is to reduce the costs of exported products with policy instruments consistent with World Trade Organization (WTO) rules.